LITERASI DIGITAL PENDIDIKAN TENGKA : ANALISIS AKSIOLOGI PESAN-PESAN MORAL DALAM AKUN YOUTUBE MATA PENA - Pipin Nafisah; Nasiruddin Nasiruddin (Kuttab : Jurnal Ilmu Pendidikan Islam, 2022)
Tengka is a social ethic for the Madurese community that is preserved and passed down from generation to generation as the basis and principle in life behavior. In the local language, tengka tade' ketabheh is interpreted as a moral message through parents' speech as advice. This study aims to reveal the new Tengka phenomenon, which is no longer obtained through speech culture but has shifted through the Mata Pena youtube account. This study uses a descriptive qualitative method with a descriptive approach to the youtube account. The primary data source is obtained from Mata Pena's youtube channel or account. This study found that the moral messages contained in the Mata Pena youtube account are human values, including thunder tolang as parembegen tengka. Mother is used as a sacred entity which is symbolized as luck and blessing in life. Obedience to parents does not have to wait to be rich; fellow brothers and sisters should not seize right and wrong. Winning and losing does not exist in the concept of humanity because no one will win, only shame on others.